Communicating for results a guide for business and the professions - Hamilton, Cheryl (Wadsworth, Cengage Learning, 2014)
"This best-selling text will show you the basic concepts and techniques you need to successfully communicate in today's business world, regardless of your current level of business experience. Covering every aspect of the communication process, Communicating For Results: A Guide for Business and the Professions, tenth edition, will give you a competitive edge in any business situation -- from the initial interview to making skilled presentations (complete with professional visual aids) to assuming a leadership role. In addition, you'll find online video clips of common professional scenarios paired with the concepts from the text give you a realistic glimpse into the business world. Communicating For Results: A Guide for Business and the Professions, tenth edition, is your opportunity to see how theory translates into practical action -- and how that knowledge will help you improve your chance of career success!"--From the publisher.